POLA KOMUNIKASI PENGGUNA DATING APPS (BUMBLE)DENGAN LINGKUNGAN SOSIAL DI KOTA MALANG - Nafillatul Izza; Faizah Ulumi Firdausi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The advancement of information technology and the widespread use of smartphones have shifted the patterns of human social interaction from physical spaces to digital platforms. One of the growing phenomena among the younger generation is the utilization of online dating applications, such as Bumble. This study aims to determine the characteristics of the social environment of dating app users in Malang City and analyze the communication patterns formed through user interactions, as well as their impact on real-world social relationships. This study employed a qualitative approach. Informants were selected using a purposive sampling technique, targeting active Bumble users in Malang City, predominantly consisting of college students and individuals within the productive age group. Data collection was conducted through digital questionnaire instruments (Google Forms), direct observation, and structured in-depth interviews. The analysis of social interaction phenomena in this study was examined through the lens of Peter Blau's Social Exchange Theory. he results of the study indicate that the motivations for using Bumble vary widely, ranging from seeking romantic partners and expanding friendship networks to merely finding entertainment. The established communication begins digitally through the in-app chat features, which may subsequently transition to other social media platforms (such as WhatsApp and Instagram) and eventuate in face-to-face (offline) meetings. Based on Peter Blau's Social Exchange Theory, the continuity of these digital interpersonal relationships is heavily influenced by reciprocal emotional and social rewards, such as mutual comfort, attention, and psychological support. If the interaction yields expected rewards, the relationship is maintained; conversely, if it causes discomfort, the relationship tends to dissolve. Furthermore, the study revealed social barriers in the form of persistent negative stigma within society, prompting some users to remain selective or conceal their dating app activities within family environments or specific public spaces.